2011
DOI: 10.1159/000335101
|View full text |Cite
|
Sign up to set email alerts
|

The ESF Meeting on „The Proteomics, Epigenetics and Pharmacogenetics of Pendrin“

Abstract: Human pendrin (SCL26A4, PDS) is a 780 amino acid integral membrane protein with transport function. It acts as an electroneutral, sodium-independent anion exchanger for a wide range of anions, such as iodide, chloride, formate, bicarbonate, hydroxide and thiocyanate. Pendrin expression was originally described in the thyroid gland, kidney and inner ear. Accordingly, pendrin mutations with reduction or loss of transport function result in thyroid and inner ear abnormalities, manifested as syndromic (Pendred syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Recent studies have demonstrated that not only loss of function, but also up-regulation of pendrin activity might play a key role in the onset of several human disorders [5], underlying the necessity for reliable tools for quantitative detection of membrane-expressed pendrin under different patho/physiological conditions. FRET technology was first described as a powerful tool for studying protein-protein interactions in living cells [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that not only loss of function, but also up-regulation of pendrin activity might play a key role in the onset of several human disorders [5], underlying the necessity for reliable tools for quantitative detection of membrane-expressed pendrin under different patho/physiological conditions. FRET technology was first described as a powerful tool for studying protein-protein interactions in living cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…These biophysical properties are fundamental to the multiple physiological functions of the transporter and its involvement in many pathological processes. In line with this, pendrin is expressed in different tissues and organs such as the thyroid, kidney, inner ear, mammary gland, testis, placenta, endometrium, lung, ameloblasts and liver [4,5,6,7]. Loss of function mutations in pendrin protein cause Pendred syndrome, an autosomal recessive inherited disease characterized by severe bilateral hearing loss, inner ear anomalies and a partial iodide organification defect that may lead to the development of euthyroid goiter or hypothyroidism [8,9,10,11].…”
Section: Introductionmentioning
confidence: 96%
“…Pendrin (SLC26A4), an exchanger transporting anions, such as chloride, bicarbonate and iodide [1,2,3], is expressed in a wide variety of tissues, including thyroid gland, inner ear, kidney, lung, liver and heart [4,5,6]. SLC26A4 is required for adequate development of the inner ear [7,8] and it has been suggested that the carrier is involved in thyroid iodide transport [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Pendrin Consortium was founded two years ago as a spin-off from an exploratory workshop funded by the European Science Foundation (ESF) in Leogang, Austria [1]. The members planned to meet biannually since then, alternating the location of the meeting between Europe and the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Pendrin (SLC26A4, PDS) is a transport protein whose malfunction or up regulation may be associated with the onset or exacerbation of a broad spectrum of diseases, including syndromic or non-syndromic deafness, hypertension, asthma and chronic obstructive pulmonary disease (COPD). “Proteomics” within this collaboration refers to how the pendrin protein alone or in conjunction with other proteins impacts the observed function; “epigenetics” refers to how inherited genetic information and genetic information not encoded in the DNA sequence translates to variations in the overall function of pendrin; and finally, “pharmacogenetics” explores how genetic differences in the pendrin gene could be translated into differences in the way that possible drugs affect pendrin function [1]. …”
Section: Introductionmentioning
confidence: 99%